Manejo de cicatrices patológicas excesivas en el Servicio de Rehabilitación - Cerda A., Lorena; Villanueva C., Valeria; Román Q., América; Contreras A., Josefina (Revista Hospital Clínico Universidad de Chile, 2018)
The excessive pathological scars are subdivided into hypertrophic, keloid and contracted.They have a complex pathophysiology, not entirely known that only exists in humans. Althoughthe frequency of presentation is not high, excessive pathological scars can affect severalareas of human functioning, in the first level of functions and body structures and in the secondlevel of activities of daily life and participation. The evaluation of patients must be complete,including the scar, and any other affected body system, together with psychological, functionaland socioeconomic factors. In the treatment of excessive scars there are multiple optionsthat must be combined for a better result. The non-surgical treatments of the most usedscars are the pressotherapy, silicone plates, intralesional injections and laser. There are otherrehabilitation treatments that although without solid evidence could have a role in patients. Thereferral to the rehabilitation service is recommended for patients with excessive pathologicalscars located in areas of folds or special areas and / or, which are accompanied by pain,alterations in the function of the body segment or limitations in activities of daily life, forcomprehensive assessment and multidisciplinary management.